Are the modified "simple questions" a valid and reliable measure of health related quality of life after stroke?. Issue 4 (1st October 2000) - Dorman, Paul; Dennis, Martin; Sandercock, Peter
Abstract : OBJECTIVES: Two "simple questions" were developed as a minimalist measurement tool to assess outcome in large trials and epidemiological studies after stroke. A previous study of their validity had disclosed ambiguities in their wording. In this study, the clarity, validity, and reliability of a modified version of these simple questions were examined. The relation between patients' responses to these questions and two widely used generic measures of health related quality of life were also studied. METHODS: A hospital based stroke register cohort of 152 patients, who were all visited at home by a study nurse, was used to study validity. A cohort of 1753 patients derived from the International Stroke Trial was used to study the relation with measures of quality of life. The sensitivity, specificity, and accuracy with which responses to each question predicted the patients' outcome measured using standard instruments was assessed. The distribution of scores for the EuroQol and SF-36 was examined for patients classified as dependent, independent, and fully recovered by the combined use of the modified simple questions. RESULTS: The modified "dependency" question had excellent sensitivity (>85%), specificity (>79%), and accuracy (>82%) for identifying dependency after stroke. The "problems" question had good sensitivity (65–88%) and moderate specificity (36–72%) for the detection of problems in a broad range of domains. The combined use of the modified dependency and problems questions provided a valid, simple, and reliable overall indicator of health related quality of life after stroke. CONCLUSIONS: The modified simple questions have excellent face validity and good measurement properties for the assessment of outcome after stroke. They are particularly well suited for large epidemiological studies and randomised trials.